Pharmacology and applications of chinese materia medica. vol. II / [Edited by] Hson-Mou Chang; Paul P H But - But, Paul P. H.edited
This book is the second volume of a comprehensive 2-volume book covering modern pharmacological and clinical studies of the most commonly used Chinese herbal drugs. It contains monographs of 127 kinds of the most commonly used Chinese Materia Medica. The information on each herb was compiled by a research specialist active in the scientific investigation of that particular type of herb. The description on each drug includes an introduction (source, character and taste, actions and indications according to traditional Chinese medicine etc.), chemical composition, pharmacology, clinical studies,